Development Of Lead-free Tungsten Carbide-based Polymeric Bricks As Gamma Radiation Shielding - Abualroos, Nadin J D (2022)
Lead bricks are the most widely used form of gamma ray shields in diagnostic radiology, radiotherapy, and nuclear medicine departments. However, lead is heavy, toxic, and dangerous to human health. Polymer-based radiation shields can be utilised in radiation shielding field due to their excellent physical and chemical properties, ease of fabrication, low manufacturing costs, and toughness. Also, their radiation shielding properties can be improved by using high atomic number fillers. The purpose of this research was to develop a lead-free tungsten carbide-based polymeric bricks as gamma radiation shielding. The fabrication of tungsten carbide-based polymeric composites involved mixing tungsten carbide powder and tungsten carbide cobalt powder with epoxy resin at different weight percentages (60, 65, 70, 75, 80, 85, 90) of fillers. Also, addition of bismuth oxide and barium sulphate powder to tungsten carbide-based epoxy matrix were studied. The physical, morphological, chemical, mechanical, and photon shielding properties were investigated for all the fabricated composites. The most optimum powder epoxy combination among all samples were 85 and 90 weight percentage of fillers. The microstructural analysis indicated that the fillers distributed uniformly within the epoxy matrix. Some agglomerations were observed for composites having more than 75 wt% of filler. Fourier transform infrared spectroscopy was used to study the chemical properties of the fabricated composites. FTIR absorption spectrum of each sample analysed in the range of 600-4000 cm-1. The results obtained did not show any spectral change for all samples.